Berberine and Oligomeric Proanthocyanidins Exhibit Synergistic Efficacy Through Regulation of PI3K-Akt Signaling Pathway in Colorectal Cancer - Okuno, Keisuke; Garg, Rachana; Yuan, Yate-Ching; Tokunaga, Masanori; Kinugasa, Yusuke; Goel, Ajay (Frontiers in Oncology, 2022)
Background: Naturally occurring dietary botanicals offer time-tested safety and anti-cancer efficacy, and a combination of certain compounds has shown to overcome the elusive chemotherapeutic resistance, which is of great significance for improving the mortality of patients with colorectal cancer (CRC). Accordingly, herein, we hypothesized that berberine (BBR) and oligomeric proanthocyanidins (OPCs) might regulate synergistically multiple oncogenic pathways to exert a superior anti-cancer activity in CRC. Methods: We performed a series of cell culture studies, followed by their interrogation in patient-derived organoids to evaluate the synergistic effect of BBR and OPCs against CRC. In addition, by performing whole genome transcriptomic profiling we identified the key targeted genes and pathways regulated by the combined treatment. Results: We first demonstrated that OPCs facilitated enhanced cellular uptake of BBR in CRC cells by measuring the fluorescent signal of BBR in cells treated individually or their combination. The synergism between BBR and OPCs were investigated in terms of their anti-tumorigenic effect on cell viability, clonogenicity, migration, and invasion. Furthermore, the combination treatment potentiated the cellular apoptosis in an Annexin V binding assay. Transcriptomic profiling identified oncogene MYB in PI3K-AKT signaling pathway might be critically involved in the anti-tumorigenic properties of the combined treatment. Finally, we successfully validated these findings in patient-derived CRC tumor organoids. Conclusions: Collectively, we for the first time demonstrate that a combined treatment of BBR and OPCs synergistically promote the anti-tumorigenic properties in CRC possibly through the regulation of cellular apoptosis and oncogene MYB in the PI3K-Akt signaling pathway.